Pengaruh Kualitas Produk, Brand Image Dan Promosi Terhadap Minat Beli Ulang Pada Minuman Teh Botol Sosro Di Depok - Siwi Afinni Lestari; Suadi Sapta Putra; Kumba Digdowiseiso (Journal of Economic, Bussines and Accounting (COSTING), 2023)
This study aims to determine the effect of product quality, brand image and promotion on repurchase interest in the bottled drinks in Depok. The sample in this study was 100 respondents who filled out the questionnaire data that I distributed by google formular media, this study used primary data with data collection methods through questionnaires distributed to 100 respondents. The data analysis technique was using inferential analysis with multiple linear regression and using the Statistical product and service solution (SPSS) version 24.0 program. From the results of multiple linear regression analysis shows that the Product Quality variable (X1) has an influence of 0.451 or 45.5%, the brand image variable (X2) has an influence of 0.194 or 19.4% and the Promotion variable (X3) has an influence of 0.196 or 19.6% of repurchase interest. Thus, it can be concluded that the variables of product quality, brand image and promotion influence purchasing decisions together. Keywords: Product Quality, Brand Image, Promotion and Repurchase Interest.